ANALYSIS OF THE LEVEL OF ROAD DAMAGE ON THE TEUKU UMAR – DR WAHIDIN SUDIROHUSODO TUBAN (3.5 Km) USING THE PAVEMENT CONDITION INDEX (PCI) METHOD - Riskiya Nurul Jannah (Civil Infrastructure Engineering and Architectural Design, 2022)
Roads are the most important aspect for the sustainability of distribution and economy, therefore it is necessary to have a review carried out so that the road remains in good condition for use. Many roads are still damaged, one of which is the Teuku Umar – Dr Wahidin Sudirohusodo road. Therefore, visual observations will be made by referring to the Pavement Condition Index (PCI) method. From the observation process, the types of damage that occurred were Cracking, Patholes, Raveling, Patching, Polished Aggregators, Rutting, Depression, and Bleeding. Where the damage rate refers to the PCI method of 38.6 and is dominated by cracking damage of 43.56% so that the repair method that can be taken is crack filling.